2014
DOI: 10.1038/ncomms5833
|View full text |Cite
|
Sign up to set email alerts
|

A novel Plasmodium-specific prodomain fold regulates the malaria drug target SUB1 subtilase

Abstract: The Plasmodium subtilase SUB1 plays a pivotal role during the egress of malaria parasites from host hepatocytes and erythrocytes. Here we report the crystal structure of full-length SUB1 from the human-infecting parasite Plasmodium vivax, revealing a bacterial-like catalytic domain in complex with a Plasmodium-specific prodomain. The latter displays a novel architecture with an amino-terminal insertion that functions as a 'belt', embracing the catalytic domain to further stabilize the quaternary structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(62 citation statements)
references
References 62 publications
5
57
0
Order By: Relevance
“…Therefore, we tested if knockdown of PfERC affects processing of PfSUB1. This protease is processed twice, once in the ER, where it undergoes a Ca 2+ -dependent autocatalytic processing from its zymogen form (83-kDa) into a 54-kDa semi-proenzyme form (p54) (25, 26, 43). From the ER, SUB1 is transported to the egress-related secretory vesicles, the exonemes, which are secreted into the PV to initiate breakdown of the PV membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tested if knockdown of PfERC affects processing of PfSUB1. This protease is processed twice, once in the ER, where it undergoes a Ca 2+ -dependent autocatalytic processing from its zymogen form (83-kDa) into a 54-kDa semi-proenzyme form (p54) (25, 26, 43). From the ER, SUB1 is transported to the egress-related secretory vesicles, the exonemes, which are secreted into the PV to initiate breakdown of the PV membrane.…”
Section: Resultsmentioning
confidence: 99%
“…It is proposed that during secretion of SUB1, it is processed by PMX from its semi-proenzyme form (p54) to its mature form (p47) (23, 24). The secretion of mature p47 form of SUB1 initiates the breakdown of the PVM (22, 43). We hypothesized that PfERC is required for the first Ca 2+ -dependent autoprocessing of SUB1, in the ER, from the 82-kDa zymogen into the p54 semi-proenzyme.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Indeed, three-dimensional homology modeling using Phyre 2 revealed a highly significant (100% confidence) structural similarity of the predicted peptidase S8 domain region to Plasmodium vivax SUB1 (PvSUB1) (15) and Plasmodium falciparum SUB1 (16). The homology model, built upon the highest-scoring template (PDB code 4TR2) corresponding to the catalytic domain of PvSUB1, comprises 9 α-helices and 10 β-strands arranged in the α/β-fold–αβ-sheet sandwiched between two prominent surface α-helices, which is typical for subtilisin-like proteins (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the P . falciparum PfSUB1 and Plasmodium vivax PvSUB1 x‐ray crystal structures were recently made available (Giganti et al, ; Withers‐Martinez et al, ). Because no structurally similar proteases have been identified in the human genome, the development of highly selective SUB1 inhibitors appears feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Several P. falciparum SUB1-specific inhibitors have been developed (Gemma et al, 2012;Giovani et al, 2014;Kher et al, 2014) and in some cases were shown to be effective in inhibiting parasite emergence from erythrocytes, indicating that SUB1 is a druggable target. In addition, the P. falciparum PfSUB1 and Plasmodium vivax PvSUB1 x-ray crystal structures were recently made available (Giganti et al, 2014;Withers-Martinez et al, 2014). Because no structurally similar proteases have been identified in the human genome, the development of highly selective SUB1 inhibitors appears feasible.…”
Section: Discussionmentioning
confidence: 99%